Viral load suppression and retention in care among children and adolescents receiving multi-month anti-retroviral therapy refills: a program data review in Uganda - Ainembabazi, Bridget; Ssebunya, Rogers N; Akobye, Winnie; Mugume, Alexander; Nahirya-Ntege, Patricia; Birungi, Denise J; Maganda, Albert K; Elyanu, Peter J; Kiragga, Dithan (BioMed Central Ltd, 2024)
Abstract Background In July 2022, Uganda’s Ministry of Health extended the 2021 WHO guidelines that recommended 3–6 monthly dispensing of antiretroviral therapy (ART) to include all children and adolescents living with HIV (CALHIV). Treatment outcomes following this recommendation have not yet been documented. We compared viral load (VL) suppression and retention in HIV care rates among CALHIV receiving 1, 2–5, and >  = 6 monthly ART dispensation in Uganda. Methods A cross-sectional study of electronic medical records in 118 health facilities was conducted. Data for CALHIV 10–19 years captured at their most recent five clinic visits as of 15th May 2023 were analysed. Most recent two VL < 1000 copies/ml were used as measures for VL suppression and sustained VL suppression. A client was considered retained in care if they visited the clinic within 28 days from their expected return visit date. We used margins plots and a modified poisson model adjusting for facility level clustering to assess VL suppression and retention across multi-month ART categories. Results A total of 2864 CALHIV, 1609 (56.2%) being females and with a median age of 12 years (inter quartile range, iqr = 7) were included. Overall suppression and retention rates were 80.4% (2133/2654) and 87.8% (2514/2864) respectively. A significant number had been dispensed ART for ≥ 2 months (50%, 2–5 months and 43.5%, ≥ 6 months). Probability of having a suppressed VL was higher among CALHIV that had received ≥ 6 months and 2–5 months of ART compared to those of 1 month i.e., 83% vs 79% vs 41% respectively. Probability of being retained in care didn’t differ across multi-month ART categories. CALHIV who received ART for 2–5 months and ≥ 6 months compared to 1 month were more likely to have a suppressed VL; (adj.PR = 1.98; 95%CI:1.41, 2.80) and (adj.PR = 2.21; 95% CI:1.59, 3.05) respectively. CALHIV with a Tuberculosis diagnosis history were less likely to have a suppressed VL (adj.PR = 0.73; 95%CI:0.65,0.81), however this was not statistically significantly different between multi-month categories. Conclusion CALHIV receiving multi-month ART including 6 months dispensation had better VL suppression rates. Retention rates however didn’t differ by multi-month dispensing categories as observed among adults in the interval trial. We recommend multi-month ART dispensation including more than 6 months among CALHIV irrespective of their age, clinical stage, and history of prior co-morbidities.